Mythologizing the Story of Creation in Indaba, My Children - Lamees Younis (Miṣriqiyā, 2021)
This paper aims at studying the story of the creation of the universe in Book One of the Bantu Text Indaba, My Children (1964) in an attempt to contextualize it within parallel creation myths from other traditions and cultures. The paper proves that the text under study is a creation myth, which is viewed as a sacred text with a cosmogonic function: to inform about the creation of the universe. To achieve this end, the researcher compares the common motifs recurrent in two of the most famous creation myths: the Book of Genesis of the Hebrew Bible and the Babylonian creation myth known as the Enûma Eliš on one hand, and the ones found in Indaba, My Children on the other. These motifs are the sexual act as a means of creation, the human form of the first creative being, bringing order after a state of chaos, and creation out of the feeling of loneliness. Through comparing those recurrent motifs in the above-mentioned texts, the researcher asserts that creation myths, even if they are geographically apart, share certain motifs and features that distinguish all of them.